No coração da escola médica : um estudo preliminar da empatia na formação médica - Silva, Andre Luiz da (2015)
The general objective of this very present dissertation is to assess the agreeableness of medical students through validation of the Big Five Inventory - 10 (IBGFP-5) in Brazil. The IBGFP-5 is a brief self-report inventory, composed by 11 items and designed to assess dimensions of personality based upon Big Five Personality Factor model, which are: Openness to Experience, Conscientiousness, Extroversion, Agreeableness (in this study, as a synonym of empathy) and Neuroticism. Such model has been replicated in several countries in the world, including Brazil. The specific objectives of this study are: (1) validating IBGFP-5 through test and retest analysis (time reliability); (2) to do crossed correlation of the IBGFP-5 as a shorter version of the IGFP-5; (3) to do convergent validaty with the Interpersonal Reactivity Index of Davis (EMRI), which assess only empathy; (4) to assess the internal consistence of the five dimensions of the IBGPF-5 in the total sample of respondents and subsets represented by the five cohorts of students, from the first to the sixth year; (5) evaluate evidences of agreeableness based upon differences of IBGFP-5 factors scores, in social and demographic variables and concerning another personality traits; and (6) discuss possible factors that may influence the development of empathy along medical school at FAMED/PUCRS. The total sample, after eliminating missing data, was composed by 200 respondents, medical students at PUCRS, most of them are female (60,5%), with mean age of 22 years old. Using confirmatory factor analysis, the IBGFP-5 comes down to a 0,256 Cronbach’s alpha. According to time reliability, convergent validity and concurrent validity, data averaged in a general fashion low reliable psychological parameters. Concerning empathy features, in post hoc tests it were noticed differences between gender and spirituality level and empathy scores (p<0,05). Results in this study tend to construct validity of the Portuguese version of the IBGFP-5, even though it has restrictions and adjustment needs. Thus, results suggest the need of further investigation of empathy among students, since empathy is a multifactorial trait, and also communication skill training in medical school. Considering the fact that the IBGFP-5 is a brief inventory with a short application time it can easily be used in transcultural studies. The limitations of this study are featured, as well as a future research calendar.